Optimization of disk seek operations using neural networks - La Red, D. (2002)
Disk access operations are the cause of considerable delays in the response time of computer systems. This is due to operating systems generally using the same disk scheduling algorithm, regardless of the system load or the number of requests which need serving. The main aim of this study is to show how artificial neural networks can be used to improve system performance by constantly selecting the most suitable disk scheduling algorithm according to the array of input / output requests that need serving.